Monochlorotriazinyl-β-cyclodextrin as a promising nanocarrier for pH-responsive doxorubicin delivery: Simulation and experimental validation - Zamani, Fatemeh; Dinari, Mohammad; Yazdani, Ali; Asadi, Parvin (Carbohydrate polymer technologies and applications, 2025)
In this investigation, the ability to form host-guest complexes of monochlorotriazinyl-β-cyclodextrin (MCT-β-CD) as a drug delivery system for Doxorubicin (DOX) was investigated by theoretical and experimental studies. Initially, the interaction of doxorubicin with MCT-β-CD was examined with molecular docking and molecular dynamics simulation. Therefore, four isomers of MCT-β-CD were considered and the best conformation of DOX in the MCT-β-CD cavity Based on lowest energy was obtained through molecular docking and for better understanding the interactions molecular dynamic simulation was employed. Analysis of the lowest binding energy obtained from the molecular docking and molecular dynamics simulation, it was demonstrated that MCT-β-CD has strong and stable complex formation with DOX. Then, in the experimental section, first, DOX was encapsulated within the MCT-β-CD to validate the theoretical findings. The structure and morphology of MCT-β-CD: DOX complex was investigated by FT-IR, XRD, SEM, and TGA analyses. Drug loading was performed and the best encapsulation efficiency was 64 %. After 24 h, 48 % of DOX was released in the acidic environment (pH=5.4), while 25 % was released in the neutral environment (pH=7.4). Additionally, the MTT assay was performed to investigate the cytotoxicity of MCT-β-CD, MCT-β-CD: DOX and free DOX against MCF7 (breast cancer cell line) and L929 (healthy cells). It was discovered that the MCT-β-CD does not affect cell proliferation, while the MCT-β-CD: DOX limits cancer cell proliferation. It also demonstrated that MCT-β-CD is highly biocompatible with normal cells, showing no cytotoxicity to L929 cells.